Direct oral anticoagulants for oral anticoagulants-naïve Asian patients with atrial fibrillation and end-stage renal disease undergoing dialysis - Roh, Jae-Hyung; Kim, Yong-Giun; Kim, Doyeon; Park, Sangwoo; Park, Kyung Sun; Kim, Minsu; Hwang, Ki Won; Hwang, Wonmook; Park, Gyung-Min; Lee, Jae-Hwan (Scientific reports, 2024)
In Asian patients with atrial fibrillation (AF) and end-stage renal disease (ESRD) undergoing dialysis, the use of direct oral anticoagulants (DOACs) remains debatable. From the national health insurance claims data in South Korea, we included 425 new users of OAC among patients with non-valvular AF and ESRD undergoing dialysis between 2013 and 2020. Patients were categorized into DOAC (n = 106) and warfarin group (n = 319). Clinical outcomes, including ischemic stroke, myocardial infarction (MI), intracranial hemorrhage (ICH), and gastrointestinal (GI) bleeding, were compared between the two groups using inverse probability of treatment weighting (IPTW) analysis. During the median follow-up of 3.2 years, the incidence of ischemic stroke was significantly reduced in the DOAC compared to the warfarin group [Hazard ratio (HR) 0.07; P = 0.001]. However, the incidence of MI (HR 1.32; P = 0.41) and GI bleeding (HR 1.78; P = 0.06) were not significantly different between the two groups. No ICH events occurred in the DOAC group, although the incidence rate did not differ significantly between the two groups (P = 0.17). In Asian patients with AF and ESRD undergoing dialysis, DOACs may be associated with a reduced risk of ischemic stroke compared with warfarin. The MI, ICH, and GI bleeding rates may be comparable between DOACs and warfarin.